2017
DOI: 10.1128/aac.00252-17
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin Dried Blood Spot Assay for Use in Patients Receiving Intramuscular Benzathine Penicillin G and Other Penicillin Preparations To Prevent Rheumatic Fever

Abstract: Rheumatic heart disease (RHD) remains an important global health challenge. Administration of benzathine penicillin (BPG) every 3 to 4 weeks is recommended as a secondary prophylaxis to prevent recurrent episodes of acute rheumatic fever and subsequent RHD. Following intramuscular injection, BPG is hydrolyzed to penicillin G (benzylpenicillin). However, little is known of the pharmacokinetics (PK) of BPG in pediatric populations at high risk of RHD or of the pharmacokinetic-pharmacodynamic relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Penicillin concentrations were assayed using a validated liquid chromatography-mass spectroscopy (LC-MS) assay. [ 25 ] Quality control samples for accuracy and inter- and intra-day variation for across concentrations between 2.5–1000 ng/mL confirmed the assay performance. The assay limits of quantification (LOQ) and detection (LOD) were 1 and 0.5 ng/mL, respectively.…”
Section: Methodsmentioning
confidence: 74%
“…Penicillin concentrations were assayed using a validated liquid chromatography-mass spectroscopy (LC-MS) assay. [ 25 ] Quality control samples for accuracy and inter- and intra-day variation for across concentrations between 2.5–1000 ng/mL confirmed the assay performance. The assay limits of quantification (LOQ) and detection (LOD) were 1 and 0.5 ng/mL, respectively.…”
Section: Methodsmentioning
confidence: 74%
“…However, there is no guidance on the optimal populations, sample size, and reportable outcome requirements for clinical validation studies, sometimes termed bridging studies. Our approach is that, in addition to demonstration of in vitro feasibility and suitability of a microsampling assay, population-specific PK bridging studies should ideally be performed in healthy volunteers (7,8) and accessible patients with the infection of interest (15). This would confirm that, in addition to adequate correlations between plasma and DBS concentrations, important PK parameters also accord in clinical settings of interest.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have shown that oral penicillin V for 10 days or a single dose of parenteral penicillin G was the first line of antibiotics to treat GAS pharyngitis and it was reduced the duration of the symptom ( 23 , 24 ). In addition, another study has reported that penicillin antibiotic treatment within 9 days was sufficient to prevent rheumatic fever ( 25 ). In contrast, other studies have proved that treatment of GAS pharyngitis by amoxicillin, erythromycin, oral cephalosporins and clindamycin for 7 days was sufficient to reduce the symptoms ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%